2022
DOI: 10.1093/nar/gkac097
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation cues in nucleosome geometry, stability and unwrapping

Abstract: Cytosine methylation at the 5-carbon position is an essential DNA epigenetic mark in many eukaryotic organisms. Although countless structural and functional studies of cytosine methylation have been reported, our understanding of how it influences the nucleosome assembly, structure, and dynamics remains obscure. Here, we investigate the effects of cytosine methylation at CpG sites on nucleosome dynamics and stability. By applying long molecular dynamics simulations on several microsecond time scale, we generat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 75 publications
5
22
0
Order By: Relevance
“…Euchromatin and heterochromatin are known to exhibit distinct chemical modifications and interact with different regulatory proteins , and nuclear bodies. , The chemical modifications themselves could drive chromatin demixing by altering nucleosome interactions. For example, acetylation could neutralize the positive charges on histone tails to weaken their binding with DNA, while methylation may lead to undertwisted DNA that strengthens its interactions with histones. , It is conceivable that nucleosomes with similar histone marks share more favorable interactions, driving their separation from other differentially modified ones. On the other hand, chromatin regulators associated with specific histone marks often contain intrinsically disordered regions that exhibit multivalent interactions to undergo liquid–liquid phase separation themselves. These proteins may further contribute to the compartmentalization of various chromatin types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Euchromatin and heterochromatin are known to exhibit distinct chemical modifications and interact with different regulatory proteins , and nuclear bodies. , The chemical modifications themselves could drive chromatin demixing by altering nucleosome interactions. For example, acetylation could neutralize the positive charges on histone tails to weaken their binding with DNA, while methylation may lead to undertwisted DNA that strengthens its interactions with histones. , It is conceivable that nucleosomes with similar histone marks share more favorable interactions, driving their separation from other differentially modified ones. On the other hand, chromatin regulators associated with specific histone marks often contain intrinsically disordered regions that exhibit multivalent interactions to undergo liquid–liquid phase separation themselves. These proteins may further contribute to the compartmentalization of various chromatin types.…”
Section: Introductionmentioning
confidence: 99%
“…For example, acetylation could neutralize the positive charges on histone tails to weaken their binding with DNA, 34−37 while methylation may lead to undertwisted DNA that strengthens its interactions with histones. 38,39 It is conceivable that nucleosomes with similar histone marks share more favorable interactions, driving their separation from other differentially modified ones. On the other hand, chromatin regulators associated with specific histone marks often contain intrinsically disordered regions that exhibit multivalent interactions to undergo liquid−liquid phase separation themselves.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DNA damage also increase histone degradation ( Hauer and Gasser, 2017 ) and histone tail cleavage has been associated with various cellular processes ( Yi and Kim 2018 ). All-atom computational modeling shows that histone tail dynamics modulate the DNA accessibility ( Armeev et al, 2021 ; Peng et al, 2021 ) and DNA methylation leads to more curved under-twisted DNA ( Li et al, 2022 ). Taking these factors into account, one might predict dramatic differences between the biophysical properties of aged chromatin versus young chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…1d ). Previous microsecond-long simulations and quantitative modeling showed that canonical nucleosomes exhibited spontaneous DNA unwrapping for systems without histone tails 32 34 . The roles of histone tails in DNA unwrapping will be discussed in the next sections.…”
Section: Resultsmentioning
confidence: 99%